A transfer alignment algorithm based on combined double-time observation of velocity and attitude. Issue 4 (13th July 2022) - Sheng, Guangrun; Liu, Xixiang; Wang, Zixuan; Pu, Wenhao; Wu, Xiaoqiang; Ma, Xiaoshuang
Abstract : Purpose: This paper aims to present a novel transfer alignment method based on combined double-time observations with velocity and attitude for ships' poor maneuverability to address the system errors introduced by flexural deformation and installing which are difficult to calibrate. Design/methodology/approach: Based on velocity and attitude matching, redesigning and deducing Kalman filter model by combining double-time observation. By introducing the sampling of the previous update cycle of the strapdown inertial navigation system (SINS), current observation subtracts previous observation are used as measurements for transfer alignment filter, system error in measurement introduced by deformation and installing can be effectively removed. Findings: The results of simulations and turntable tests show that when there is a system error, the proposed method can improve alignment accuracy, shorten the alignment process and not require any active maneuvers or additional sensor equipment. Originality/value: Calibrating those deformations and installing errors during transfer alignment need special maneuvers along different axes, which is difficult to fulfill for ships' poor maneuverability. Without additional sensor equipment and active maneuvers, the system errors in attitude measurement can be eliminated by the proposed algorithms, meanwhile improving the accuracy of the shipboard SINS transfer alignment.